Comparative mitochondrial genomics reveals a possible role of a recent duplication of NADH dehydrogenase subunit 5 in gene regulation. (6th August 2018) - Li, Runsheng; Ren, Xiaoliang; Bi, Yu; Ding, Qiutao; Ho, Vincy Wing Sze; Zhao, Zhongying
Abstract: Mitochondrial genome (mtDNA) carries not only well-conserved protein coding, tRNA and rRNA genes, but also highly variable non-coding regions (NCRs). However, the NCRs show poor conservation across species, making their function and evolution elusive. Identification and functional characterization of NCRs across species would be critical for addressing these questions. To this end, we devised a computational pipeline and performed de novo assembly and annotation of mtDNA from 19 Caenorhabditis species using next-generation sequencing (NGS) data. The mtDNAs for 14 out of the 19 species are reported for the first time. Comparison of the 19 genomes reveals species-specific sampling of partial displacement-loop (D-loop) sequence as a novel NCR inserted into a unique tRNA cluster, suggesting an important role of the D-loop and the tRNA cluster in shaping NCR evolution. Intriguingly, RNA-Seq analysis suggests that a novel NCR resulting from a recent duplication of NADH dehydrogenase subunit 5 ( ND5 ) could be utilized as a 3′ UTR for up-regulation of its upstream gene. The expression analysis shows a species- and sex-specific expression of mitochondrial genes encoded by mtDNA and nucleus, respectively. Our analyses provide important insights into the function and evolution of mitochondrial NCRs and pave the way for further studying the function and evolution of mitochondrial genome.